New & improved . finley flowers - Young, Jessica; Secheret, Jessica (North Mankato, MN Picture Window Books, an Capstone imprint, 2016)
For their first assignment in fourth grade Finley has to think of an invention that will help the world--but when her Supersonic Sibling Sublimator appears to work too well, and her annoying older brother vanishes, only to reappear laughing at the trick he played, Finley comes up with a new invention she is sure will be a hit
1 2 13
Keywords: Brothers and sisters -- Juvenile fiction; Inventions -- Juvenile fiction; Middle-born children -- Juvenile fiction